Characterization techniques for tobacco and its derivatives: a systematic review - Shen, Kai; Xia, Liwei; Jiao, Kaixuan; Pan, Fanda; Xiang, Boka; Zhou, Wei; Shou, Yuedian; Gao, Xuefeng; Hu, Shihao; Fang, Haoyu; Xia, Chen; Jiang, Xinru; et al. (Frontiers in Chemistry, 2024)
Biomass and its derivatives have broad applications in the fields of bio-catalysis, energy storage, environmental remediation. The structure and components of biomass, which are vital parameters affecting corresponding performances of derived products, need to be fully understood for further regulating the biomass and its derivatives. Herein, tobacco is taken as an example of biomass to introduce the typical characterization techniques in unraveling the structural information, chemical components, and properties of biomass and its derivatives. Firstly, the structural information, chemical components and application for biomass are summarized. Then the characterization techniques together with the resultant structural information and chemical components are introduced. Finally, to promote a wide and deep study in this field, the perspectives and challenges concerning structure and composition charaterization in biomass and its derivatives are put forward.